Vmeasur: A software package for experimental and clinical measurement of mesenteric lymphatic contractile function over an extended vessel length. (10th February 2022) - Russell, Peter S.; Hucklesby, James J. W.; Hong, Jiwon; Cao, Enyuan; Trevaskis, Natalie L.; Angel, Catherine E.; Windsor, John A.; Phillips, Anthony R. J.
Abstract: Objective: Conventionally, in vivo mesenteric lymphatic contractile function is measured using a high magnification transmission microscope (field of view 0.3–1.5 mm), which precludes visualization of extended lengths of vessels embedded in mesenteric fat. Existing software is not optimized for imaging at a low magnification using a contrast agent. We aimed to develop a simple and clinically transferable method for in situ visualization, image analysis, and quantitative assessment of mesenteric lymphatic contractile function over an extended area. Methods: Subserosal injection of various blue dyes was taken up by mesenteric lymphatics and visualized under a stereomicroscope (25×), allowing for video recording of 1.4 × 1.1 cm of intact mesentery. A new R package ("vmeasur") that combines multiple high‐performance image analyses into a single workflow was developed. The edges of each vessel were determined by applying an automated threshold to each frame (with real‐time manual verification). The vessel width at every point in each frame was plotted to provide contractile parameters over time and along the lymphatic vessel length. Results: Contractile parameters and their differences along the length of the vessel were accurately calculated in a rodent model. In a human mesenteric lymphatic, the algorithm was also able to measure changes in diameter over length. Conclusion: This software offers a low cost, rapid, and accessible method to measure lymphatic contractile function over a wide area, showing differences in contractility along the length of a vessel. Because the presence of mesenteric fat has less of an impact on imaging, due to the use of an exogenous contrast agent, there is potential for clinical application.